Genetic Variation of EPAS1 Gene in Tibetan Pigs and Three Low-Altitude Pig Breeds in China - Kun-zhe DONG; Ye KANG; Na YAO; Guo-tao SHU; Qing-qing ZUO; Qian-jun ZHAO; Yue-hui MA (Journal of Integrative Agriculture, 2014)
Endothelial PAS domain protein 1 (EPAS1), also called hypoxia-inducible factor-2, is a key regulatory factor of hypoxic responses and plays an essential role in high-altitude adaptation in mammalian species. In this study, polymorphisms of EPAS1 were detected in 217 individuals from 2 Tibetan pig populations and 3 low-altitude pig breeds by DNA pooling, PCR-SSCP, PCR-RFLP and DNA sequencing methods. A total of 14 synonymous polymorphisms were identified in the coding region. The analysis suggested that SNP1 (G963A), SNP7 (C1632T), SNP10 (G1929A) and SNP11 (G1947A) showed potential association with high-altitude environment because of their particular variation patterns in Tibetan pigs. Linkage disequilibrium (LD) of these SNPs was analyzed. One common LD block including 5 SNPs clustering in exon 12 was identified in all studied pig populations. Haplotype H1 (AGGTC) in LD block was dominant in Tibetan pigs (76.6 and 74.2% in Linzhi (LZ) and Chayu (CY) pigs, respectively) and segregated at higher frequency than that in low-altitude pig breeds (52.3, 58.7 and 56.2% in Wuzhishan (WZS), Min (M) and Laiwu (LW) pigs, respectively), indicating that H1 may relate to adaptation to high altitude in Tibetan pigs. These findings raise hope that EPAS1 gene can be a candidate gene that involved in adaptation of high altitude in Tibetan pigs.